622. Risk Factors for 30-Day Unplanned Readmissions in Patients Discharged with Outpatient Parenteral Antimicrobial Therapy. (31st December 2020) - Shah, Megan; Kidd, Catherine; Thomas, Tania A; Eby, Joshua
Abstract: Background: Outpatient parenteral antimicrobial therapy (OPAT) programs have shown to reduce hospital readmissions; however, 20-25% of OPAT patients are readmitted. As 30-day readmissions is a healthcare quality measure, it is important to recognize predictors for readmissions in OPAT patients in an effort to minimize risk factors and optimize patient outcomes. The aim of this study was to identify modifiable and non-modifiable risk factors for 30-day unplanned readmission in patients discharged with OPAT. Methods: This was a retrospective cohort study of patients admitted to University of Virginia (UVA) Health System between March 2019 and December 2019 who were discharged home with intravenous antimicrobials followed by the UVA OPAT program. Data collected included patient demographics, comorbidities, infection diagnosis, source control, and antimicrobial class. Variables were compared between patients with a 30-day unplanned readmission and those without a readmission. Mann-Whitney U, Pearson chi-squared, and Fisher's exact tests were utilized, as appropriate. A multiple logistic regression analysis was performed to determine predictors of 30-day unplanned readmission. Results: There were 334 OPAT patients who met inclusion criteria. Median age was 58 years, 58% were male, and the most common infection diagnoses were bone/joint (49%), bloodstream (22%), and endovascular (13%). There were 64 (19%) patients who had an unplanned 30-day readmission. The most common reasons for readmission included non-infection related (45%), worsening infection (28%), and antimicrobial-related complication (17%). Readmitted patients were more likely to have a higher Charlson Comorbidity Index (CCI); prior admissions; bloodstream, endovascular, or pulmonary infection; no source control; and an infection caused by a multi-drug resistant organism. CCI was found to be an independent predictor of readmission (OR 1.096, 95% CI 1.001-1.200). Conclusion: Unplanned readmissions were common in patients discharged with OPAT. There should be an emphasis on interventions to prevent readmissions in OPAT patients, particularly those with high-risk clinical characteristics. Disclosures: All Authors : No reported disclosures